2015
DOI: 10.1038/onc.2015.333
|View full text |Cite
|
Sign up to set email alerts
|

Systematic integration of molecular profiles identifies miR-22 as a regulator of lipid and folate metabolism in breast cancer cells

Abstract: Dysregulated microRNA (miRNA) mediate malignant phenotypes, including metabolic reprogramming. By performing an integrative analysis of miRNA and metabolome data for the NCI-60 cell line panel, we identified an miRNA cluster strongly associated with both c-Myc expression and global metabolic variation. Within this cluster the cancer-associated and cardioprotective miR-22 was shown to repress fatty acid synthesis and elongation in tumour cells by targeting ATP citrate lyase and fatty acid elongase 6, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 74 publications
1
42
0
Order By: Relevance
“…miR-22 could repress fatty acid synthesis and was an important regulator of lipid and folate metabolism in breast cancer cells (Koufaris et al, 2016). miR-27a was reported to accelerate adipolysis releasing significantly more glycerol and free fatty acids (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…miR-22 could repress fatty acid synthesis and was an important regulator of lipid and folate metabolism in breast cancer cells (Koufaris et al, 2016). miR-27a was reported to accelerate adipolysis releasing significantly more glycerol and free fatty acids (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of MTHFD2 in breast cancer, as well as the association between the levels of this enzyme and poor patient prognosis, demonstrate that altered function of this enzyme confers selective advantages to tumors 2,10,12,13 . However, recent data indicate that MTHFD2 also possesses non-metabolic functions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found a significant association between mRNA expression 10,11 and protein expression of MTHFD2 in large cohorts of breast cancer patients 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a miR-22 knockout mouse model was readily available. Activation of miR-22 knockout T cells resulted in significant increases in expression of miR-22 target genes Acly (26), Pten (27), and Tet2 (28), a trend toward increased expression of putative miR-22 target genes Ets1 and Serpinb9 (Fig. 2C), and no effect on expression of a control gene (Sdha) lacking miR-22 seed sites (see Fig.…”
Section: Posttranscriptional Regulation Of Gw182 Expressionmentioning
confidence: 99%